2009
DOI: 10.1016/j.visres.2008.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Strabismic amblyopes show a bilateral rightward bias in a line bisection task: Evidence for a visual attention deficit

Abstract: Neurologically normal observers show a consistent leftward bias when asked to bisect a horizontal line ("pseudoneglect"). In this study, we found that subjects with strabismic and strabismic-anisometropic amblyopia show a consistent rightward bias ("minineglect") in a line bisection task. The bias was seen in both eyes, but affected more strongly the amblyopic eye. Purely anisometropic amblyopes show a similar bias, affecting only the amblyopic eye. The group of strabismics with alternating fixation did not di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
1
19
1
Order By: Relevance
“…Our results may appear to be at odds with previous evidence from amblyopic individuals who showed a rightward bias ("minineglect") when bisecting physical lines (Thiel & Sireteanu, 2009) and no consistent directional bias when bisecting numerical intervals (Mohr et al, 2010). It was suggested (see Mohr et al, 2010) that the pattern of performance of amblyopic individuals in bisection tasks may depend on a different organization of the dorsal visual pathway (i.e., the cortical stream that projects from early visual areas to the posterior parietal cortex, and that is involved in space perception and action control; see Milner & Goodale, 1992) Collignon, Voss, Lassonde, & Lepore, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results may appear to be at odds with previous evidence from amblyopic individuals who showed a rightward bias ("minineglect") when bisecting physical lines (Thiel & Sireteanu, 2009) and no consistent directional bias when bisecting numerical intervals (Mohr et al, 2010). It was suggested (see Mohr et al, 2010) that the pattern of performance of amblyopic individuals in bisection tasks may depend on a different organization of the dorsal visual pathway (i.e., the cortical stream that projects from early visual areas to the posterior parietal cortex, and that is involved in space perception and action control; see Milner & Goodale, 1992) Collignon, Voss, Lassonde, & Lepore, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…In line with evidence obtained with normally sighted individuals (see, e.g., Loftus et al, 2009;Longo & Lourenco, 2007), one might expect blind individuals to show a consistent leftward bias in bisecting numerical intervals. However, recent evidence has suggested that normal vision may play a different role in the directional bias that emerges in line and numerical bisection tasks: In particular, it has been shown that individuals affected by amblyopia, a developmental disorder affecting spatial vision that results in poor uniocular vision, show a "minineglect" (rightward bias) in line bisection (Thiel & Sireteanu, 2009) but no significant bias in numerical bisection (Mohr, Mues, Robol, & Sireteanu, 2010). Whether a similar dissociation exists in totally blind individuals is therefore an empirical question.…”
mentioning
confidence: 99%
“…Thiel and Sireteanu (2009) found that subjects with strabismic amblyopia showed a bilateral rightward bias in a line bisection task, reminiscent of classic attentional neglect. Our psychophysical results also indicate that the activation of motion-driven attention in untrained adult strabismic amblyopes is less when using the amblyopic eye rather than their fellow eye, or either dominant of non-dominant eye of control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, misalignment of the visual axes has long been known in animal and human studies to be associated with abnormal binocular fixation and eye movements, and deficits in visual attention (Singer, 1982a; Asper et al, 2000b; Thiel and Sireteanu, 2009; Wang et al, 2015; Hou et al, 2016). In fact, Singer (1982b) discussed the role of attention in the development of amblyopia and observed that synchronous binocular eye movements are crucial for the development of normal visual pathways (Ciuffreda et al, 1979a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of amblyopia on spatial perception have been examined using variety of tasks, including vertical alignment [58], [59], line bisection [60], [61], [62], [63], Vernier acuity [62], [64] and localization [65]. These studies reported a range of deficits in terms of distortions, as well as reduced accuracy and precision of spatial localization during amblyopic eye viewing.…”
Section: Discussionmentioning
confidence: 99%